Quantifying the role of alternative pension reforms on the Austrian economy - Miguel Sánchez-Romero; Jože Sambt; Alexia Prskawetz (Vienna University of Technology, Institute of Mathematical Methods in Economics, Research Group Economics, 2012)
This paper investigates the role of recent pension reforms for the development of the social security system and economic growth in Austria. We use a computable general equilibrium model that is built up of overlapping generations that differ by their household structure, longevity, educational attainment, and capital accumulation. Each household optimally decides over its consumption paths, work effort, and retirement age according to the life-cycle theory of labor, while they face survival risk. We find that the pension reforms implemented from 2000 to 2004, although in the correct direction, are not sufficient to solve the labor market distortion caused by the Austrian PAYG pension system. Using alternative policy options, our simulations indicate that a change to a notional defined contribution system and an increase in the educational distribution of the work force would increase the incentive for later retirement ages and thereby increase labor supply and economic growth.
Keywords: 330